Sawdust as an Environmentally Friendly Adsorbent - Aslam, Muhammad Anis; Khan, Idrees (New Environmentally-Friendly Materials, 2022)
Sawdust, an abundant byproduct of the wood processing industry, has gained attention as a sustainable, low-cost adsorbent for water and wastewater treatment. Its lignocellulosic composition—rich in cellulose, hemicellulose, and lignin—provides a variety of functional groups capable of binding a wide range of contaminants, including heavy metals, synthetic dyes, and organic pollutants. This review synthesizes current knowledge on the sources and characteristics of sawdust, modification techniques to enhance adsorption performance, mechanisms of pollutant removal, and applications across different wastewater types. Comparative analyses with conventional and other bio-based adsorbents highlight its economic and environmental advantages. Limitations and challenges for large-scale implementation are discussed, along with future research priorities to optimize performance, regeneration, and integration into hybrid treatment systems. The findings reinforce sawdust’s role as a promising material in advancing sustainable and circular water treatment technologies.